A Magic Bullet? The Potential Impact of E-Cigarettes on the Toll of Cigarette Smoking - Mendez, David (Nicotine Tob Res, 2020)
INTRODUCTION: We examine the proportion of US smoking-produced mortality that e-cigarettes might eliminate under assumptions regarding vaping’s ability to increase smoking cessation, vaping’s health risks, and the possibility that vaping will increase smoking among young people. METHODS: We employ a dynamic population simulation model that tracks individuals from ages 0 to 110, differentiated by gender and smoking status. Using data from the US Census, the National Vital Statistics Reports, Cancer Prevention Study II, and the National Health Interview Survey, we estimate the number of smoking-related life-years lost (LYL) from 2018 to 2100 in a no-vaping scenario. We then compare results for model runs that assess the impact of vaping under a variety of assumptions. RESULTS: The combination of assumptions produces 360 possible scenarios. 357 (99%) yield positive estimates of life-years saved (LYS) due to vaping by 2100, from 143 000 to 65 million. Most scenarios result in millions of individuals quitting smoking due to vaping. On average, vaping-induced quitters gain an extra 1.2–2.0 years of life compared to smokers who quit without vaping. The impact of vaping is greatest when it most helps smokers who otherwise have the greatest difficulty quitting smoking. While the numbers of LYS are generally large across all scenarios, they often represent a small fraction of the toll of smoking. CONCLUSIONS: Vaping is highly likely to reduce smoking-produced mortality. Still, vaping is not “the” answer to the public health crisis created by smoking. Rather, it may well be a tool to add to the armamentarium of effective tobacco control measures. IMPLICATIONS: E-cigarettes hold the potential to reduce cigarette smoking’s enormous toll. By itself, however, tobacco harm reduction, as embodied in vaping, is no magic bullet. Going forward, tobacco control will require vigilant application of the evidence-based measures that have brought us so much success in combatting smoking. It will require, as well, the search for and adoption of novel means of attacking the remaining problem. Harm reduction can, and many would say should, be a part of the complex formula that will eventually bring about the demise of smoking.